Observation and numerical simulation of terrain-disrupted wavy motion in the boundary layer with minor temperature inversion/isothermal at the Hong Kong international airport - CHAN, PW (MAUSAM, 2014)
Wavy motion in the boundary layer with minor temperature inversion (less than 1 degree Celsius)/isothermal for terrain-disrupted airflow at the Hong Kong International Airport is documented in the present paper. Wave magnitude of about 3 m/s near the ground increasing to 5 to 6 m/s at 200 m has been observed from the vertical velocity measurement from a minisodar on 13 April, 2012. The wavy motion is not observed from other meteorological measurements, such as conical scan of the radial velocity from a Light Detection And Ranging (LIDAR) system. It is studied in more detail using high-resolution numerical weather prediction model. It is shown in the model simulation results that the wavy motion appears to be associated with airflow disruption of the prevailing south to southwesterly winds by a mountain to the south of the airport.